Life cycle assessment for frozen food distribution schemes - Markus Trapp; Michael Lütjen; Juan Daniel Arango Castellanos; Oliver Jelsch; Michael Freitag (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
The online grocery market is facing big challenges. In addition to products for daily use, it is necessary to deliver fresh, chilled and frozen foods quickly and reliably to the customer. For decades frozen products have been delivered to the customers by using small cooling vans. Since some years, also normal parcel delivery services in combination with insulated shipping containers have been used. This article examines in a comparative analysis the environmental impact based on CO2 emissions of alternative distribution schemes (supermarket, cooling van, parcel delivery) by using a life cycle assessment (LCA) according to DIN EN ISO 14040. Thereby, the parcel delivery of insulated containers made of EPS (Expanded Polystyrene) was studied in detail, including recycling difficulties for the end customer. The LCA study showed that the transport scenario using small cooling vans lead to higher CO2 emissions, whereas the classical transport using high-capacity refrigerator trucks and refrigerated storage houses represented the scenario with less CO2 emissions. Additionally, recycling EPS-packaging in private households showed that reducing its volume is complicated and troublesome. The tests indicated that forces higher than 500 newtons were needed to break certain EPS-packaging.
urn:nbn:de:gbv:830-88217834; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; online grocery; life cycle assessment; city logistics; Expanded Polystyrene-Packaging